2013
DOI: 10.1371/journal.pone.0081502
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the RB1 Imprint

Abstract: The human RB1 gene is imprinted due to a differentially methylated CpG island in intron 2. This CpG island is part of PPP1R26P1, a truncated retrocopy of PPP1R26, and serves as a promoter for an alternative RB1 transcript. We show here by in silico analyses that the parental PPP1R26 gene is present in the analysed members of Haplorrhini, which comprise Catarrhini (Old World Monkeys, Small apes, Great Apes and Human), Platyrrhini (New World Monkeys) and tarsier, and Strepsirrhini (galago). Interestingly, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…In our study, the GFP CGI retrotransposed into Chromosome 2 was not imprinted since no change in methylation patterns was observed when it was transmitted through either the female (B1712) or male (B1718) germline. This result is not unexpected because it has been suggested that the epigenetic fate of the retrotransposed DNA depends on its sequence and selective forces at the integration site (Kanber et al 2013). …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In our study, the GFP CGI retrotransposed into Chromosome 2 was not imprinted since no change in methylation patterns was observed when it was transmitted through either the female (B1712) or male (B1718) germline. This result is not unexpected because it has been suggested that the epigenetic fate of the retrotransposed DNA depends on its sequence and selective forces at the integration site (Kanber et al 2013). …”
Section: Discussionmentioning
confidence: 64%
“…Many pseudogenes are imprinted, manifesting parent-of-origin specific methylation in the overlapping CGIs. In several cases, the imprinted intronic pseudogenes are also responsible for the imprinting of the corresponding genes that contain them (Cowley and Oakey 2010;Kanber et al 2013). In our study, the GFP CGI retrotransposed into Chromosome 2 was not imprinted since no change in methylation patterns was observed when it was transmitted through either the female (B1712) or male (B1718) germline.…”
Section: Discussionmentioning
confidence: 99%
“…The RB1 region in ID28 has been analyzed by deep bisulfite sequencing on the Roche/454 GS junior system as described previously in Kanber et al [24]. The PCR amplicon designed to CGI85 incorporates 11 CpG dinucleotides (chr13:48,893,503-48,893,690, hg19) and the average methylation value has been determined at a read depth of 3017 reads.…”
Section: Analysis Of the Rb1 And Nesp-as Region In Id28mentioning
confidence: 99%
“…The integration of this retrocopy led to RB1 imprinting as its expression is skewed in favor of the maternal allele. 16,17 RPS2P32 on chromosome 7 is derived from the gene RPS2 on chromosome 16 (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Parent-of-origin-specific methylation of CpG85 has been confirmed by other studies. [15][16][17][18] At present, nearly 100 imprinted human genes have been identified, and several studies have taken a genome-wide look at parent-of-origin-specific DNA methylation in order to identify novel imprinted genes. 18,19 Retrocopies are instructive genomic elements for studying the evolutionary dynamics and constraints of DNA methylation.…”
Section: Introductionmentioning
confidence: 99%